Unseen Burden: Lifestyle Factors Impact on Mental Health Among Khartoum University Medical Students - A Mohammed, Omer; Randa Ahmed Abdalrheem Altamih; Osman Kamal Osman Elmahi (International Journal of Medical Students, 2025)
BACKGROUND: Mental illnesses are prevalent among youths globally, with the World Health Organization reporting 800,000 suicide deaths annually, making it the second leading cause of death worldwide. This study aimed to evaluate the mental health of medical students at Khartoum University and explore the relationship between lifestyle factors and their mental status. METHODS: This descriptive, cross-sectional, institution-based study was conducted at the University of Khartoum, Faculty of Medicine. A sample of 322 medical students was selected using multistage stratified random sampling. Data were collected via a self-administered online form incorporating the General Health Questionnaire (GHQ-12) and the Depression, Anxiety and Stress Scale (DASS-21). Statistical analyses included chi-square testing and correlation analysis to examine the relationships between lifestyle factors and mental health. Results: The study found that 43.8% of the respondents experienced depression, 55.9% anxiety, and 48.5% stress. Severe stress was significantly associated with female gender (p = 0.02) and smoking (p = 0.004). Sleep disturbances were significantly linked to severe depression, stress, and anxiety (p < 0.01). Additionally, inadequate sleep was significantly associated with severe depression (p = 0.007) and stress (p = 0.031). Consuming a daily diet rich in fruits, vegetables, whole grain bread, and drinking water was associated with lower stress levels (p = 0.015 and p = 0.018, respectively). Overall, 22.6% of the students were found to be in psychological distress. A significant positive correlation was observed between GHQ-12 and DASS-21 scores for depression (r = 0.589; p < 0.001), anxiety (r = 0.538; p < 0.001), and stress (r = 0.718; p < 0.001). CONCLUSIONS: The study concluded that depression, anxiety, and stress levels are notably high among medical students at Khartoum University. Factors such as female gender, smoking, and poor sleep quality are associated with increased stress levels, while healthy dietary habits correlate with reduced stress. These findings highlight the need for establishing counseling services in medical schools, integrating mental health into the medical curriculum, and empowering medical students through support from academic staff.